A dança como expressão do imaginário - Teixeira, Carlos Henrique [UNESP]; Monteiro, Sueli Aparecida Itman [UNESP] (My University, 2012)
This article summarizes the findings obtained in ethnographic research conducted in 2009, which led to the dissertation entitled The weaving of movement: dance, tribalism and imaginary in everyday life of a group of students at a public school in Araraquara city defended the Universidade Estadual Paulista - Faculdade de Ciências e Letras de Araraquara, São Paulo. The objective of the survey was to collect clues to a method of movement analysis with reference to the Anthropology of the Imaginary Gilbert Durand and studies of efforts (effort shape) in Rudolf Laban. For this, we identified the main break dance moves practiced by a group of teens who attend school on weekends. The inventory movements in this dance led to a rhythmic and gestural thinking beyond the rationalization of bodily education.

Este artigo sintetiza as conclusões obtidas em pesquisa etnográfica realizada no ano de 2009, que deu origem à dissertação de mestrado intitulada As tessituras do movimento: dança, tribalismo e imaginário no cotidiano de um grupo de alunos de uma escola pública de Araraquara, defendida na Universidade Estadual Paulista - Faculdade de Ciências e Letras de Araraquara, São Paulo. O objetivo da pesquisa foi levantar pistas para um método de análise dos movimentos tendo como referência a Antropologia do Imaginário de Gilbert Durand e os estudos dos esforços (effort shape) em Rudolf Laban. Para isso, identificaram-se os principais movimentos da dança break praticada por um grupo de adolescentes que frequenta a escola aos finais de semana. O inventário dos movimentos desta dança nos conduziu a um pensar gestual e rítmico, para além da racionalização da educação do corpo.
Dance as expression of imaginary
Keywords: Dance; Anthropology; Imaginary; Education; Body; Dança; Antropologia; Imaginário; Educação; Corpo